(untitled) (Proceedings of International Educators Conference, 2024)
In this article, the process of organizing the meanings of words that are often used in linguistics, the methods of filling the content of the terminological dictionary, and the analysis of the means and methods of terminology formation is the systematization of the methods of word formation in many studies.